Five Things an Agricultural Producer Can Do to Improve Business Profitability - Edward Evans (EDIS)
The business of producing agricultural commodities is undergoing considerable change. Long gone are the days when an agricultural producer could afford to ignore what goes on outside the local area and still expect to make a profit. In today's world characterized by the increasing globalization of competition, producers must be cognizant of the world around them and must make informed decisions from an increasing volume of information. Improved financial management has become the single most important factor for success in a globally competitive market. This article summarizes five things that producers can do to improve the profitability of their agricultural businesses. This is EDIS document FE569, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published August 2005.